2015
DOI: 10.1037/xhp0000110
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interference on short-term memory for visual orientation.

Abstract: Visual short-term memory serves as an efficient buffer for maintaining no longer directly accessible information. How robust are visual memories against interference? Memory for simple visual features has proven vulnerable to distractors containing conflicting information along the relevant stimulus dimension, leading to the idea that interacting feature-specific channels at an early stage of visual processing support memory for simple visual features. Here we showed that memory for a single randomly orientate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
124
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(146 citation statements)
references
References 86 publications
18
124
3
1
Order By: Relevance
“…9). This finding is in line with behavioral and neuroimaging demonstrations showing higher fidelity memory recall for similar targets and distractors (Rademaker, Bloem, De Weerd, & Sack, 2015;Lorenc, Sreenivasan, Nee, Vandenbroucke, & D'Esposito, 2018; Supplementary Fig. 2).…”
Section: Figuresupporting
confidence: 76%
“…9). This finding is in line with behavioral and neuroimaging demonstrations showing higher fidelity memory recall for similar targets and distractors (Rademaker, Bloem, De Weerd, & Sack, 2015;Lorenc, Sreenivasan, Nee, Vandenbroucke, & D'Esposito, 2018; Supplementary Fig. 2).…”
Section: Figuresupporting
confidence: 76%
“…visual) 'shapes' the (visual) WM representation (Ester, Zilber, & Serences, 2015;Hakun & Ravizza, 2016;Rademaker, Bloem, De Weerd, & Sack, 2015;Yoon, et al, 2006) (however, see Awh, Vogel, & Oh, 2006;Cools, Miyakawa, Sheridan, & D'Esposito, 2010;Ester, et al, 2015;Gazzaley, Cooney, Rissman, & D'Esposito, 2005;McNab & Klingberg, 2008;Zanto & Gazzaley, 2009). Yet in the real world, distraction is often in a different modality than the target information (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Third, recent studies have found evidence that WM contains group-level information – such as statistical summary information – along with item-level information (Brady & Alvarez, 2011; 2015; Orhan & Jacobs, 2012). Fourth, WM representations are vulnerable to inference from other simultaneously stored information (Huang & Sekuler, 2010; Radenmaker, Bloem, Weerd, & Sack, 2015; Oberauer & Lin, 2017). Together, these findings question the common assumption of independence and suggest that individual items might interact in WM.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the interactions observed in most of these studies may have occurred during perception rather than reflecting interactions between WM representations per se. In other words, when multiple items are presented simultaneously, this might lead to distortions of perception or the extraction of summary properties, which are then carried forward into WM (e.g., Brady & Alvarez, 2011; 2015; Clevenger & Hummel, 2013; Orhan & Jacobs, 2013; Jiang, Olson, & Chun, 2000; Woodman, Vecera, & Luck, 2003; Xu, 2006; Xu & Chun, 2007; but see Huang & Sekuler, 2010; Kang & Choi, 2015; Rademaker et al, 2015). Little is known about whether and how visual WM representations interact with each other after the information has been encoded into WM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation